A Conceptual Framework for Mitigating Graduate Employment Problems - Amer Al Nejam; Alicia Tang Yee Chong; Mohd Sharifuddin Ahmed; Osama Al-Masri (Journal of ICT in Education, 2017)
Graduate employability has always been an issue of concern when prospective employers complain of the lack of prerequisite attributes of fresh graduates. Despite the many efforts to ease the problems, graduate employment issues continue to plague Malaysia’s labor market. We attest the veracity of this remark by the continued and prolonged social issues, as consequences of these problems, faced by many parties including government agencies, higher learning institutions, industries, parents and unemployed graduates themselves. Higher learning institutions and industries are often at odds when it comes to graduate’s quality. Parents and their unemployed children present another social problem. In our contribution to mitigate these issues, this paper proposes a conceptual framework which involves the main stakeholders related to the graduate employment issues. The cooperation between these stakeholders is key to the successful implementation of the framework that mitigates the graduate employment problems.